Training to Improve Knowledge, Skills and Behaviors of Healthcare Associated Infections Preventions in Nurses - Dewa Gede Baskara; Ni Putu Emy Darma Yanti; Ida Ayu Md Vera Susiladewi (Indonesian Journal of Global Health Research, 2020)
Hospitals can be a source of transmission of microorganisms to patients during treatment. Infections acquired by patients while being hospitalized are called Healthcare Associated Infections (HAIs), so HAIs are an indicator of the quality of care provided by the hospital. The purpose of this study is to know the effectiveness of training on the knowledge, skills, and behavior of prevention of HAIs in nurses in the hospital. A quasi-experimental research design with a pre-test and post-test design with a control group design on 140 nurses through purposive sampling was used. Data collection used questionnaires (r value 0.412-0.716> r table 0.294; Cronbach Alpha 0.753) and observation sheets. The Wilcoxon test was used to analyze the mean difference between groups because the data were not normally distributed. The mean difference between the control and intervention groups was analyzed using the Mann-Whitney test. The results of the study obtained shows the effect of training on knowledge (p value <0.001), skills (p value <0.001), and behavior (p value = 0.041) on HAI prevention in the intervention group. In fact, in the control group, it was found that there was no effect of training on knowledge, skills and behavior of prevention of HAIs (p value> 0.005). There were differences in knowledge, skills, and behavior of HAI prevention between the intervention group and the control group (p value <0.001).